Determinan Kejadian Kekurangan Energi Kronik (Kek) Pada Ibu Hamil Di Wilayah Kerja Puskesmas Siak Hulu III Kabupaten Kampar - Sintia Sintia; Winda Septiani; Novita Rany; Elmia Kursani (STIKes Hang Tuah Pekanbaru, 2021)
Chronic Energy Deficiency (CED) pregnant women is a situation where a pregnant woman experiences nutritional deficiencies (calories and protein) that have long or chronic competition. In 2018, national the prevalence of CED in pregnant women is 17,3%, and the Siak Health Center prevalence of CED deficiency in pregnant women was 21,4%. The purpose of this research was to determine the factors that influence the CED in pregnant women in the working area of the Siak Hulu III Health Center of Kampar district. The method of this research was a descriptive quantitative analytical study with a cross-sectional design. The sample was 70 respondents in the working area Puskesmas Siak Hulu III. The sampling technique was consecutive sampling with the dependent variable, namely pregnant women with CED if the upper circumference <23,5 cm, and the dependent variable was knowledge, infectious disease, family income, parity, and hyperemesis gravidarum. The data analysis was a bivariate analysis with the Chi-Square test. The instrument used questionnaires and data processing using computerized. The results showed a correlation between knowledge on pregnant women CED (p-value 0,158 OR = 2,602), the influence of infectious diseases on pregnant women CED (p-value 0,003 OR = 5,881), family income (p-value 0,025 OR = 0,231), parity) (p-value 0,025 OR = 4,333), and hyperemesis gravidarum (p-value 0,017 OR = 3,934). It can be concluded that there is an influence between infectious disease, family income, parity, hyperemesis gravidarum, and health workers, in particular, are expected to be able to provide information.Â Â